The Analysis of Monetary Transmission by Interest Rate Channel in Influencing the Inflation: VECM Approach - Zulfa, F; Aji Suseno, D (KnE Social Sciences, 2018)
Bank Indonesia set Inflation Targeting Framework from July 2005 which is communicated the inflation target to the public. However, the phenomenon showed that the actual inflation from 2005 to 2016 has not been able to achieve compliance with inflation targeting that has been set by Bank Indonesia. The purpose of this research is to know and analyze about the effectiveness of monetary policy transmission of interest rate channel in influencing inflation in Indonesia. This purpose is reflected in the inflation fluctuation response due to the shock of other macroeconomic variables and the strongest variability of macroeconomic variable used as the operational target of monetary policy transmission. Data used in this research are quarterly time series data from year 2005Q3 until 2017Q1. The variables used in this research are SBI interest rate, the rate of interbank call money market, deposit interest rate, loan interest rate, investment and output gap. Data used in this research sourced by Bank Indonesia and Badan Pusat Statistik. The method used in this research is Vector Error Correction Model (VECM). The results of impulse response function test showed that the transmission mechanism of monetary policy requires time lag to be able to influence inflation and indicate that the monetary policy transmission mechanism through the effective interest rate in influencing the ultimate goal of inflation. In addition, variance decomposition results concluded that the rate of interbank call money market variant is appropriately used as an operational target of monetary policy transmission for implementation in influencing inflation. Keywords: Transmission, Monetary Policy, Interest Rate, Inflation, VECM.